EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES THROUGH DEMONSTRATION METHODS IN MATHEMATICS LESSON MATERIALS BUILDING SPACE - Mardhiah, Ainal (Faculty of Tarbiyah nad Teacher Training, 2023)
This study aims to examine efforts to improve student learning outcomes through demonstration methods in mathematics subjects with building materials in the form of blocks and cubes for fourth grade students of MIN 26 Pidie. This type of research uses classroom action research (CAR), with subjects covering 37 fourth grade students at MIN 26 Pidie. The results of this study conclude that the application of the demonstration method can improve the learning outcomes of fourth grade students at MIN 26 Pidie in mathematics lessons on building materials (cubes and blocks). This is evidenced by the results of the student's pre-test which was originally low, namely 38.64 (none even completed according to the Minimum Completeness Criteria/KKM). The results of the final test in the first cycle that did not use the demonstration method (still conventional method) showed an increase, where 7 students had achieved the KKM score (18.9%) while the other 30 students had not reached the KKM (81.1%). Furthermore, the results of the final test in the second cycle that had used the demonstration method showed a significant increase, where there were 32 students (86.48%) who met the KKM and 5 students (13.52%) who had not reached the KKM.